Pelaporan Ziswaf Pada Laz al Hijrah Kota Medan Berdasarkan PSAK 109 - Ismi Affandi; R Riswanto (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
This research is about Ziswaf Reporting on Laz Al Hijrah in Medan based on statement of financial accounting standards 109. This research was conducted to find out about the suitability of the application statement of financial accounting standards 109 on the reporting of Ziswaf OPZ institution Laz Al Hijrah Fund in Medan 2015. The data used in this study is secondary data and primary. Secondary data was obtained from the Laz AL Hijrah Financial report and the primary data was obtained through the results of interviews with the Director of Laz AL Hijrah, Medan. The research method used is a method with a type of qualitative research that the results of the research are delivered by means of exposure. The results of the study show that: Laz Al Hijrah, Medan City, North Sumatra, has not implemented the preparation of financial statements in accordance with the format of the zakat, infaq/ alms financial accounting report contained in the Statement of Financial Accounting Standards number 109, because for the compilation of Laz Al Hijrah only refers according to the direction and needs of Laz Al Hijrah whose form is still a report on the receipt and distribution of zakat, all cash funds that go to Laz Al Hijrah in Medan, North Sumatra have not been separated by zakat funds, infaq funds / sedakah, and amil, and non-halal funds, although they do not follow the financial report format set by the Indonesian Institute of Accountants, but in general the purpose of preparing financial statements for the Medan City of North Sumatra has been achieved, provided there are certain information not clear.